Performance of hypersaline brine desalination using spiral wound membrane: A parametric study - Foo, Kathleen; Liang, Y. Y.; Lau, W. J.; Rahman Khan, Md Maksudur; Ahmad, Abdul Latif (MDPI, 2023)
Desalination of hypersaline brine is known as one of the methods to cope with the rising global concern on brine disposal in high-salinity water treatment. However, the main problem of hypersaline brine desalination is the high energy usage resulting from the high operating pressure. In this work, we carried out a parametric analysis on a spiral wound membrane (SWM) module to predict the performance of hypersaline brine desalination, in terms of mass transfer and specific energy consumption (SEC). Our analysis shows that at a low inlet pressure of 65 bar, a significantly higher SEC is observed for high feed concentration of brine water compared with seawater (i.e., 0.08 vs. 0.035) due to the very low process recovery ratio (i.e., 1%). Hence, an inlet pressure of at least 75 bar is recommended to minimise energy consumption. A higher feed velocity is also preferred due to its larger productivity when compared with a slightly higher energy requirement. This study found that the SEC reduction is greatly affected by the pressure recovery and the pump efficiencies for brine desalination using SWM, and employing them with high efficiencies (ηR ≥ 95% and ηpump ≥ 50%) can reduce SEC by at least 33% while showing a comparable SEC with SWRO desalination (<5.5 kWh/m3).